Deferasirox for iron chelation in multitransfused children with sickle cell disease; long‐term experience in the East London clinical haemoglobinopathy network. (24th September 2014) - Tsouana, Eva; Kaya, Banu; Gadong, Nimze; Hemmaway, Claire; Newell, Heather; Simmons, Andrea; Whitmarsh, Simon; Telfer, Paul
Abstract: Deferasirox (DFX) has been licensed for iron chelation in patients with sickle cell disease (SCD), but there is limited data on its long‐term efficacy and safety in children. This retrospective study included 62 regularly transfused children managed in the East London and Essex Clinical Haemoglobinopathy Network (mean age 9.2 ± 3.2 yr). Efficacy measurements consisted of monthly serum ferritin (SF) and annual R2 MRI‐estimated liver iron concentration (LIC), and safety markers included serum creatinine and alanine aminotransferase (ALT). The mean duration of DFX treatment was 2.5 ± 1.4 yr, and mean dose at 36 months was 25 mg/kg/d. Mean SF at initiation of treatment was 2542 ± 952 ng/mL and increased to 4691 ± 2255 ng/mL at 36 months ( P  = 0.05). Mean LIC on first scan was 10.3 mg/g dry weight and did not decrease significantly on follow‐up scans. There was a significant correlation between relative change in LIC and in SF ( R 2  = 0.66, P  < 0.001). Reversible transaminitis episodes, probably due to drug‐induced hepatitis, were noted in 53% of patients. Responses to an adherence and acceptability questionnaire indicated that more than 50% of children had difficulties in taking DFX, commonly because of unpleasant taste. Our results show that more than 50% of children with SCD have inadequate control of iron overload with DFX. It is not clear whether this is because of frequent dose interruptions, poor tolerability and adherence, or poor efficacy of the drug. We recommend further studies to confirm these findings and to optimise iron chelation in this population.